Stress Ratio Effects in Fatigue of Lost Foam Cast Aluminum Alloy 356 - (:unkn) unknown (My University, 2014)
Lost foam casting is a highly versatile metalcasting process that offers significant benefits in terms of design flexibility, energy consumption, and environmental impact. In the present work, the fatigue behavior of lost foam cast aluminum alloy 356, in conditions T6 and T7, was investigated, under both zero and non-zero mean stress conditions, with either as-cast or machined surface finish. Scanning electron microscopy was used to identify and measure the defect from which fatigue fracture initiated. Based on the results, the applicability of nine different fatigue mean stress equations was compared. The widely-used Goodman equation was found to be highly non-conservative, while the Stulen, Topper-Sandor, and Walker equations performed reasonably well. Each of these three equations includes a material-dependent term for stress ratio sensitivity. The stress ratio sensitivity was found to be affected by heat treatment, with the T6 condition having greater sensitivity than the T7 condition. The surface condition (as-cast vs. machined) did not significantly affect the stress ratio sensitivity. The fatigue life of as-cast specimens was found to be approximately 60 - 70% lower than that of machined specimens at the same equivalent stress. This reduction could not be attributed to pore size alone, and is suspected to be due to the greater concentration of pyrolysis products at the as-cast surface. Directions for future work, including improved testing methods and some possible methods of improving the properties of lost foam castings, are discussed.
Keywords: Aluminum; Fatigue; Lost Foam; Mean Stress; Metalcasting